A Lean-Based Simulation Approach to Setup Changeover Improvement on the Flexo 8 Machine Using Single-Minute Exchange of Dies (SMED) Method - Febrian, Nanda Dwi; Amalia, Amalia (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2025)
Production efficiency is a crucial element in enhancing the competitiveness of manufacturing industries. One common challenge is the lengthy setup changeover time, which leads to downtime and reduced productivity. This study aims to propose an improvement to the setup changeover process on the Flexo 8 machine at PT APP Purinusa Eka Persada-Semarang by implementing the Single-Minute Exchange of Die (SMED) method combined with Arena simulation software. The research was conducted through direct observation, data collection of setup times during January–March 2024, and analysis using the SMED approach, which includes separation of internal and external activities, conversion of internal to external activities, and simplification of setup tasks. Subsequently, a simulation model was developed using Arena software to compare the conditions before and after SMED implementation. The simulation results indicate that the SMED method successfully reduced the average setup changeover time from 52.67 minutes to 35.13 minutes, representing a 33.3% reduction. These findings confirm that the SMED approach can simplify setup processes, reduce downtime, and improve resource efficiency. The study recommends integrating SMED with simulation as an effective strategy for optimizing production processes. However, this research is limited by the exclusion of external activities in the simulation and the reliance on the accuracy of observational data. Future studies may expand the analysis to examine the impact of SMED on cost and product quality.